Factors influencing the turnover of frontline public child welfare supervisors. Issue 5 (19th October 2020) - Griffiths, Austin; Murphy, April; Desrosiers, Patricia; Harper, Whitney; Royse, David
ABSTRACT: Frontline child welfare supervisors are a vitally important component for providing leadership in service delivery and workforce stability. This statewide study of public child welfare supervisors uses a modified version of a previously developed instrument (the CWEFS) to examine job satisfaction and factors influencing supervisors' intention to leave. A consistent negative perception of salary was found but a stratified pattern of dissatisfaction emerged across other variables when examined by intention to leave (Stayers, Undecided, and Leavers). A Hierarchical Binary Logistic Regression Model identified two factors that predicted intention to leave: dissatisfaction with administrative support and workload impact.